Attributions of LGBTQ+ Identity and Religious Views on Homosexuality to Disaffiliation from Orthodox Judaism - Gennady Vulakh; Rona Miles; Alla Chavarga; Estee Hirsch; Pesach Eisen (Religions, 2023)
Religious disaffiliation has been found to occur at higher rates in LGBTQ+ individuals than in heterosexual individuals and in the general population. In this brief report, we explore whether LGBTQ+ people who disaffiliated from Orthodox Judaism attributed sexual identity and/or Orthodox Judaism’s lack of acceptance of homosexuality to their disaffiliation. This analysis focuses on 117 individuals who identified as LGBTQ+ who were drawn from a larger study that included 387 participants across all sexual orientations who disaffiliated from Orthodox Judaism. Unexpectedly, only 18 of the respondents reported that their sexual identity and/or religious views on homosexuality were causes for their disaffiliation. A lack of education and language around LGBTQ+ concepts in ultra-Orthodox Jewish communities may have contributed to this finding. We suggest that additional research be conducted to explore the complex relationship between LGBTQ+ identity and disaffiliation from Orthodox Judaism.